Bilateral hip dysplasia – a case report in a 66-year-old man - Wróbel, Grzegorz (Journal of Education, Health and Sport, 2018)
Hip dysplasia in adults occurs when the defect was not treated in childhood or when the treatment was ineffective. The main symptoms include swelling, redness of the joint area and pain, which intensifies during exercise, there may also be limping. In the image examinations, the outline of the joint may be distorted. Hip dysplasia is usually diagnosed by an experienced physician using the combination of symptoms, hip examination and x-ray findings. A computed tomography may also be helpful to diagnose hip dysplasia and give the physician information on any damage to the cartilage and labrum. A 66-year-old man with symptoms of constant pain in the hip area, which intensifies when walking, standing or running. Pain at night during rest and the impression of catching, slamming or blocking. As a result of the study, the features of bilateral dysplasia of the hip joints with large degenerative changes in the joints and periarticular calcifications was observed.